2020
DOI: 10.1111/lam.13369
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect on anti‐methicillin‐resistantStaphylococcus aureusamong combinations of α‐mangostin‐rich extract, lawsone methyl ether and ampicillin

Abstract: Significance and impact of the study: The impact of this study is to overcome the problem on the treatment of MRSA using the antibacterial cocktails of α-mangostin-rich extract and lawsone methyl ether or each of them in combination with ampicillin. The significance of this study is an achievement of finding for the antibacterial cocktails prepared by a green technology that is practically used for commercialization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…Also, ARE (1Á95-7Á81 µg/ml) and LME (0Á49-1Á95 µg/ml) enhanced anti-MRSA activity of ampicillin (0Á49 µg/ml) against all four MRSA isolates, with the FICI values of 0Á039-0Á257 and 0Á016-0Á039, respectively. The result of synergistic anti-MRSA effect of LME and ampicillin agrees with the previous report by Meah et al (2020). The present study revealed two new combinations for anti-MRSA, i.e., ARE plus LME and ARE plus ampicillin.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Also, ARE (1Á95-7Á81 µg/ml) and LME (0Á49-1Á95 µg/ml) enhanced anti-MRSA activity of ampicillin (0Á49 µg/ml) against all four MRSA isolates, with the FICI values of 0Á039-0Á257 and 0Á016-0Á039, respectively. The result of synergistic anti-MRSA effect of LME and ampicillin agrees with the previous report by Meah et al (2020). The present study revealed two new combinations for anti-MRSA, i.e., ARE plus LME and ARE plus ampicillin.…”
Section: Resultssupporting
confidence: 92%
“…Cell membrane disruption ability was determined using the crystal violet uptake assay and was confirmed with a determination of the release of 260 nm-absorbing materials, an indicator of bacterial membrane damage. A release of UV-absorbing material at 260 nm indicates the leakage of the intracellular components of MRSA (Meah et al 2020). Based on the crystal violet uptake assay, ARE, LME and ampicillin caused the alteration of cell membrane of MRSA by significantly increasing the crystal violet uptake in treated bacteria when compared to the negative control (Fig.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations